Measurement of soil-water characteristic curve using the evaporation method and the dew point method - Wang, Yuying (2016)
The knowledge of hydraulic retention function is essential for various purposes, such as for estimating unsaturated hydraulic conductivity. However, the measurement of soil-water characteristic curve (SWCC) using the conventional method, such as Tempe Cell or hanging column, can be time consuming and labour intensive. The simplified evaporation method was proposed by Schindler (1980) to determine soil hydraulic properties, such as soil-water characteristic curve and hydraulic conductivity curve, at wet to moderately dry range. The dew point method was used to determine the dry range of SWCC. In this project, the reliability of these two novel approaches was evaluated for a broad spectrum of soil textures ranging from clay to pure sand. The simplified evaporation method (HYPROP©) was compared with the traditional measurement method, Tempe Cell. The results from both methods were generally well matched for the entire measurement range. The validity of dew point method (WP4C PotentiaMeter®) was confirmed as the data points (suctions measured > 500 kPa) obtained by this approach provided a good continuation of SWCCs obtained by HYPROP or Tempe Cell. However, the dew point method had a tendency to overestimate soil suctions at low suction range. This phenomenon was more pronounced for soil with less cohesion.